DIFICULDADE DE APRENDIZAGEM: A ESCOLA, O EDUCANDO E A FAMÍLIA - Silva, Kênia Ribeiro da (2010)
Despite of innumerable studies about the theme difficulty in learning and exhausting efforts, a long history of Education, to find explanations, of the causes of not being able to learn, consider it relevant, still today, to address it, considering that this subject was not yet enlightened. Once problems in learning persist and manifests in different ways in the scene of Brazilian education. This work investigates this subject expliciting the discussion of the difficulty in learning present in the pedagogical Brazilian since the Republic. Considering on an analysis this facts, the concept of learning based on a conception of Lev. Vigotsky on a cultural historic perspective, also on Bernard Chariot about knowing and the relation that the person establishes with knowing, and the explications on Philippe Meirieu about the process of elaboration of knowledge begins. Discusses also the concept of Difficulty of Learning taking as reference theoretical Pierre Bourdieu about the function the school in the capitalists societies. Throughout the empirical research made in two public schools in Goiânia and the starting from the method and the analysis the facts the present dissertation explicit as the school and theirs educators, the students and the families understand, explains and analysis the difficulty in learning and how it articulates between the cultural capital and the academic knowledge required by schools in relation on the learning of the student. The data show a pedagogical relationship between teachers and students fragile and inefficient, whose teaching practice does not contribute to realization of a meaningful learning.The school attributes the cause of learning difficulties to factors external to it, thus contributing to the reproduction of educational inequalities and hence to social inequalities.